"Caring About Me": a pilot framework to understand patient-centered care experience in integrated care - a qualitative study. Issue 7 (27th July 2020) - Youssef, Alaa; Wiljer, David; Mylopoulos, Maria; Maunder, Robert; Sockalingam, Sanjeev
Abstract : Objective: The aim of this study is to examine patients' experiences in integrated care (IC) settings. Design: Qualitative study using semistructured interviews. Settings: Two IC sites in Toronto, Canada: (1) a community-based primary healthcare centre, supporting patients with hepatitis C and comorbid mental health and substance use issues; and (2) an integrated bariatric surgery programme, an academic tertiary care centre. Participants: The study included patients (n=12) with co-occurring mental and physical health conditions. Seven participants (58%) were female and five (42%) were male. Methods: Twelve indepth semistructured interviews were conducted with a purposeful sample of patients (n=12) with comorbid mental and physical conditions at two IC sites in Toronto between 2017 and 2018. Data were collected and analysed using grounded theory approach. Results: Four themes emerged in our analysis reflecting patients' perspectives on patient-centred care experience in IC: (1) caring about me; (2) collaborating with me; (3) helping me understand and self-manage my care; and (4) personalising care to address my needs. Patients' experiences of care were primarily shaped by quality of relational interactions with IC team members. Positive interactions with IC team members led to enhanced patient access to care and fostered personalising care plans to address unique needs. Conclusion: This study adds to the literature on creating patient-centredness in IC settings by highlighting the importance of recognising patients' unique needs and the context of care for the specific patient population.